1996
DOI: 10.1152/jn.1996.76.5.3503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dynamic spectra in ferret primary auditory cortex. I. Characteristics of single-unit responses to moving ripple spectra

Abstract: 1. Auditory stimuli referred to as moving ripples are used to characterize the responses of both single and multiple units in the ferret primary auditory cortex. Moving ripples are broadband complex sounds with a sinusoidal spectral profile that drift along the logarithmic frequency axis at a constant velocity. 2. Neuronal responses to moving ripples are locked to the phase of the ripple, i.e., they exhibit the same periodicity as that of the moving ripple profile. Neural responses are characterized as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
253
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(273 citation statements)
references
References 21 publications
20
253
0
Order By: Relevance
“…For the dynamic-ripple stimuli (Kowalski et al, 1996a;Depireux et al, 2001) shown in Figure 2A, each stimulus is composed of a single spectrotemporal modulation frequency (Fourier component). It can therefore be considered the auditory equivalent to the drifting sinusoidal luminance gratings used in visual neuroscience (Valois and Valois, 1990).…”
Section: Dynamic-ripple Stimulimentioning
confidence: 99%
“…For the dynamic-ripple stimuli (Kowalski et al, 1996a;Depireux et al, 2001) shown in Figure 2A, each stimulus is composed of a single spectrotemporal modulation frequency (Fourier component). It can therefore be considered the auditory equivalent to the drifting sinusoidal luminance gratings used in visual neuroscience (Valois and Valois, 1990).…”
Section: Dynamic-ripple Stimulimentioning
confidence: 99%
“…The spatial organization of tuning to broad-band ripple spectra should be related to sharpness of tuning assessed with pure-tones since both reflect aspects of spectral filtering (Calhoun and Schreiner, 1998;Wang and Shamma, 1995). However, there is only sparse experimental evidence for spatial organization of ripple transfer functions Kowalski et al, 1996). In this study, care was taken to sample the targeted frequency region evenly to avoid spatial biases due to sharpness of tuning clusters.…”
Section: Physiology Of Ripple Spectramentioning
confidence: 99%
“…broad-band stimuli with sinusoidal spectral envelopes similar to the structure of vowels, have been used to characterize spectral integration properties of central auditory neurons (e.g., Schreiner and Calhoun, 1994;Shamma et al, 1995;Klein et al, 2000;Miller et al, 2002;Escabi and Schreiner, 2002). Cat and ferret cortical neurons respond preferentially to a narrow range of formant ratios or spectral envelope frequencies (Calhoun and Schreiner, 1998;Klein et al, 2000;Kowalski et al, 1996;Schreiner and Calhoun, 1994;Shamma et al, 1995). Receptive field properties determined with broad-band acoustic gratings and pure tones appear to be related, although the precise nature of that relationship is still debated (Calhoun and Schreiner, 1998;Linden et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of multiple auditory cortical areas on the ectosylvian gyrus (EG) of this species was first demonstrated by using 2‐deoxyglucose autoradiography (Wallace et al, 1997) and subsequently confirmed by using optical imaging of intrinsic signals (Nelken et al, 2004) and single‐unit recording (Kelly et al, 1986; Kelly and Judge, 1994; Kowalski et al, 1995; Bizley et al, 2005). Although most electrophysiological recording studies have focused on the primary auditory cortex (A1) (Phillips et al, 1988; Kowalski et al, 1996; Schnupp et al, 2001; Fritz et al, 2003; Rabinowitz et al, 2011; Keating et al, 2013), the nonprimary auditory fields in this species are now receiving increasing attention (Nelken et al, 2008; Bizley et al, 2009, 2010, 2013; Walker et al, 2011; Atiani et al, 2014). …”
mentioning
confidence: 99%